Pengaruh E-Wom, Food Quality, dan Resto Atmosphere Terhadap Keputusan Pembelian di Resto My Tora Chicken Makamhaji: Studi pada Masyarakat di Kabupaten Sukoharjo - Siti Maesaroh; Gunarso Wiwoho (LP3M Universitas Putra Bangsa, 2023)
This study aims to determine the effect of E-WOM, food quality, and restaurant atmosphere on purchasing decisions at My Tora Chicken Makamhaji Resto in Sukoharjo. Collecting data in this study using a questionnaire. Respondents in this study were 110 consumers who had made a purchase at My Tora Chicken Makamhaji Restaurant. This study used descriptive analysis techniques and statistical analysis, including validity tests, reliability tests, classical assumption tests, multiple linear regression analysis, t tests, f, and the coefficient of determination using SPSS. The results of this study indicate that E-WOM has an influence but not significant on purchasing decisions, but there is a positive and significant influence between food quality and restaurant atmosphere on purchasing decisions. And there is a positive and significant influence between E-WOM, food quality, and restaurant atmosphere together on purchasing decisions at My Tora Chicken Makamhaji Resto in Sukoharjo.